Verfassungen für ein modernes Europa? Untersuchungen zu Konstitutionalisierungsprozessen in Frankreich, Polen-Litauen und im Großherzogtum Toskana am Ende des 18. Jahrhunderts. Vergleich und Analyse - Alexander Piff (Historia.scribere, 2012)
The following seminar-paper compares two constitutions and one concept of a constitution from the end of the 18th century. Considering the first French constitution, the Constitution Française from 1791, the first “modern” European constitution, the polish Ustawa rządowa (adopted as “Government Act”) also from 1791 and a concept for a constitution initialized and elaborated by the Grand Duke of Tuscany (the last version dates from 1787), Pietro Leopoldo, the comparison will be accomplished by using four different categories describing the political and philosophical circumstances which influenced the writing of the constitutions.